2012
DOI: 10.3138/jvme.0712-065r
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Depression and Anxiety, General Health, and Academic Performance in Three Cohorts of Veterinary Medical Students across the First Three Semesters of Veterinary School

Abstract: This study builds on previous research on predictors of depression and anxiety in veterinary medical students and reports data on three veterinary cohorts from two universities through their first three semesters of study. Across all three semesters, 49%, 65%, and 69% of the participants reported depression levels at or above the clinical cut-off, suggesting a remarkably high percentage of students experiencing significant levels of depression symptoms. Further, this study investigated the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
2
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(116 citation statements)
references
References 71 publications
6
100
2
8
Order By: Relevance
“…A variety of other mediating and/or comorbid factors such as socioeconomic status, mental health (anxiety and depression in particular), cultural and family values, stress handling capability, peer pressure, intelligence quotient (IQ), tobacco smoking etc can play a major role in determining academic performance in college students [19, 22, 26–29]. …”
Section: Introductionmentioning
confidence: 99%
“…A variety of other mediating and/or comorbid factors such as socioeconomic status, mental health (anxiety and depression in particular), cultural and family values, stress handling capability, peer pressure, intelligence quotient (IQ), tobacco smoking etc can play a major role in determining academic performance in college students [19, 22, 26–29]. …”
Section: Introductionmentioning
confidence: 99%
“…There is substantial evidence that shows veterinary students have increased stress, anxiety, and depression during their training, and is oftentimes associated with pressure to perform academically (Kogan et al, 2005;Zenner et al, 2005;Hofmeister et al, 2010;Reisbig et al, 2012). These stress, anxiety, and depressive behaviors within veterinary students are often found to be elevated within the first year (Hafen et al, 2006;Hafen et al, 2008), when anatomy courses are, historically, a large component of their curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…Academic stress negatively contributed to depression and anxiety symptoms, life satisfaction, academic performance, and general health of the students. [5] In medical students, 14.3% reported moderate to severe depression, and depression was stigmatized. [6] Loneliness is a newer concept of interest that has been explored little in college-age students.…”
Section: Psychosocial Concerns Among Studentsmentioning
confidence: 99%
“…[43] Even at the professional degree levels, up to 69% of students reported significant levels of depressive symptoms, and academic stress was attributed to depression and anxiety symptoms, life satisfaction, academic performance, and general health. [5] Furthermore, a recent systematic review indicated high prevalence of anxiety, depression, and psychological distress in medical students, ranging from 6% to 97%, but little has been studied about the causes or consequences. [44] Although depression and anxiety levels seem to be relatively low in our study, given potential serious consequences (e.g., suicide) [4] even with mild and moderate levels of depressive symptoms, [3] regular monitoring and availability of counseling resources may be beneficial.…”
Section: Psychosocial Profilementioning
confidence: 99%